High tolerance of a high-arctic willow and graminoid to simulated ice encasement - Bjerke, Jarle W.; Elverland, Ellen; Jaakola, Laura; Lund, Leidulf; Zagajewski, Bogdan; Bochenek, Zbigniew; Kłos, Andrzej; Tømmervik, Hans (Boreal Environment Research Publishing Board, 2018)
Source at http://www.borenv.net/BER/ber231-6.htm . Climate change-induced snow thaw and subsequent accumulation of ice on the ground is a potential, major threat to snow-dominated ecosystems. While impacts of ground-ice on arctic wildlife are well explored, the impacts on tundra vegetation is far from understood. We therefore tested the vulnerability of two high-arctic plants, the prostrate shrub Salix polaris and the graminoid Luzula confusa , to ice encasement for 60 days under full environmental control. Both species were tolerant, showing only minor negative responses to the treatment. Subsequent exposure to simulated late spring frost increased the amount of damaged tissue, particularly in S. polaris , compared to the pre-frost situation. Wilting shoot tips of S. polaris increased nearly tenfold, while the proportion of wilted leaves of L. confusa increased by 15%. During recovery, damaged plants of S. polaris responded by extensive compensatory growth of new leaves that were much smaller than leaves of non-damaged shoots. The results suggest that S. polaris and L. confusa are rather tolerant to arctic winter-spring climate change, and this may be part of the reason for their wide distribution range and abundance in the Arctic.